Hydrolytic enzymes and antibiotic sensitivity of Xanthomonas oryzae pv. oryzae, incitant of bacterial leaf blight of rice in West Bengal - S. HANSDA, S.K. RAY*, K.D. TAMANG, S. DUTTA and (Indian Phytopathology, 2016)
Two virulent isolates of Xanthomonas oryzae pv. oryzae ( Xoo-Wb and Xoo-Nd) were selected for this experimental assay after pathogenecity test on susceptible rice cv. Swarna (MTU-7029) following standard bacteriological inoculation technique. Different enzymatic activities (cellulase, amylase, lipase, protease and pectinase etc.) of the isolates were carried out in vitro to evaluate role of hydrolytic enzymes in pathogenesis. Sensitivity of these isolates towards 24 antibiotics were assayed to find out the best one (s) for field application. Experimental findings in in vitro assay revealed that both the isolates Xoo-Wb and Xoo-Nd exhibited high cellulase, amylase, lipase, protease and pectinase activity indicated by halo zone diameter. Among 24 antibiotics tested through Hi-Media antibiotic discs, Norfloxacin (10 mcg and 300 mcg), Gentamicin (10 mcg), Co-Trimoxazole (25 mcg), Kanamycin (30 mcg), Tetracycline (30 mcg), Streptomycin (100 mcg) and Chloramphenicol (30mcg) were found to be effective antibiotics against Xoo isolates and may be advocated under field condition for BLB management.